Development of Motion Graphic Video Media History of Herman's Government Willem Daendels (1808-1811) in Learning Indonesian History For Increasing Students' Interest in Learning for High School - Sa'adah, Iffah; Pramono, Suwito Eko; Suharso, R (Universitas Negeri Semarang, 2020)
The research objectives are as follows: (1) To describe the history of learning in Indonesia in SMA Negeri 1 Bangsri. (2) To produce learning media through motion graphic video History of Government Herman Willem Daendels (1808-1811) developed in SMA Negeri 1 Bangsri. (3) To know and motion graphic History of Government Herman Willem Daendels (1808-1811) worthy of learning media. (4) To know the effectiveness of using learning media in the form of a motion graphic video History of Government Herman Willem Daendels (1808-1811) was seen from the average student’s interest in SMA Negeri 1 Bangsri. The type of research conducted is Research and Development (R&D). The results showed the development of learning media in the form of motion graphic video History of Government Herman Willem Daendels (1808-1811) between traffic (1) The process of learning History of Indonesia was done in SMA Negeri 1 Bangsri. (2) The development of learning media in the form of motion graphic video History of Government Herman Willem Daendels (1808-1811) was conducted in three main stages: preliminary, study stage, development, and evaluation. (3) Based on validation done by material and media experts, motion graphics are suitable for use as a learning medium in school. (4) Motion graphic video History of Government Herman Willem Daendels (1808-1811) is compelling for use in learning History of Indonesia class XI in SMA Negeri 1 Bangsri.